Clinical Characterization of Arrhythmia-Induced Cardiomyopathy in Patients With Tachyarrhythmia and Idiopathic Heart Failure - Schach, Christian; Körtl, Thomas; Zeman, Florian; Luttenberger, Bianca; Mühleck, Franziska; Baum, Paul; Lavall, Daniel; Vosshage, Nicola H.; Resch, Markus; Ripfel, Sarah; Meindl, Christine; Ücer, Ekrem; et al. (My University, 2024)
Background: Arrhythmia-induced cardiomyopathy (AIC) is a known entity, but prospective evidence for its characterization is limited. Objectives: This study aimed to: 1) determine the relative frequency of the pure form of AIC in the clinically relevant cohort of patients with newly diagnosed, otherwise unexplained left ventricular systolic dysfunction (LVSD) and tachyarrhythmia; 2) assess the time to recovery from LVSD; and 3) identify parameters for an early diagnosis of AIC. Methods: Patients were prospectively included, underwent effective rhythm restoration, and were followed-up at 2, 4, and 6 months to evaluate clinical characteristics, biomarkers, and cardiac imaging including cardiac magnetic resonance imaging. Patients with recurred arrhythmia were excluded from analysis. Results: 41 of 50 patients were diagnosed with AIC 6 months after rhythm restoration. Left ventricular (LV) ejection fraction increased 2 months after rhythm restoration from 35.4% ± 8.2% to 52.7% ± 8.0% in AIC patients vs 37.0% ± 9.5% to 43.3% ± 7.0% in non-AIC patients. From month 2 to 6, LV ejection fraction continued to increase in AIC patients (57.2% ± 6.1%; P < 0.001) but remained stable in non-AIC patients (44.0% ± 7.8%; P = 0.628). Multivariable logistic regression analysis revealed that lower LV end-diastolic diameter at baseline could be used for early diagnosis of AIC, whereas biomarkers and other morphological or functional parameters, including late LV gadolinium enhancement, did not show suitability for early diagnosis. Conclusions: We observed a high prevalence of AIC in patients with otherwise unexplained LVSD and concomitant tachyarrhythmia, suggesting that this condition may be underdiagnosed in clinical practice. Most patients recovered fast, within months, from LVSD. A low initial LV end-diastolic diameter may constitute an early marker for diagnosis of AIC.
Keywords: ddc:610